Scratch induced thin film buckling for quantitative adhesion measurements. (5th October 2018) - Kleinbichler, A.; Pfeifenberger, M.J.; Zechner, J.; Wöhlert, S.; Cordill, M.J.
Abstract: Adhesion of thin films is one of the most important factors determining reliability of microelectronic devices and semiconductor industry requires quantitative testing methods to effectively compare these interfaces. Several techniques have been developed over the last decades with scratch induced delamination being a rarely studied method. For compressively stressed films on rigid substrates scratching can cause buckling failure and by modeling the delaminations according to the Hutchinson and Suo model the adhesion can be determined quantitatively. Two different sample systems, a tungsten-titanium film on a silicate glass and a silicon nitride film on a silicate glass with a tungsten-titanium overlayer, have been tested using scratch loads in the range of 100–500 mN. This study demonstrates that the scratching resulted in buckles parallel to the scratch trace and triggered further spontaneous buckling. Using the dimensions of the induced buckles the interfacial adhesion energies were quantified. The adhesion energy of the tungsten‑titanium/silicate glass interface was measured to be 2.7 J/m 2 and of the silicon nitride/silicate glass interface was 1.5 J/m 2 . The results illustrate that the scratch test can be utilized for quantitative adhesion testing of thin films and suggest that scratch induced delamination is a valuable addition to established adhesion measurement techniques. Graphical abstract: Unlabelled Image Highlights: Two film systems were scratched in a load range of 100-500 mN using a Berkovich tip. Buckles developed parallel along the scratch trace and were the point of origin for spontaneous telephone cord buckles. The adhesion energies of two film systems could be quantified using the dimensions of the parallel and spontaneous buckles.